PENGEMBANGAN MEDIA PEMBELAJARAN KARTU HURUF UNTUK ANAK DIDIK DI TK BUNGA BANGSA KECAMATAN PAKAL SURABAYA - Ida Ariyanti; Hirnanda Dimas Pradana (Educational Technology Journal, 2023)
This research uses a type of development research (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to design effective learning by making letter cards for kindergarten-aged children. The research subjects were teachers and students of Bunga Bangsa Kindergarten. The results of this study indicate that the use of letter card learning media increases student involvement in learning and helps students to be able to read beginning. Product development in the form of letter cards is based on product needs in learning at Bunga Bangsa Kindergarten. The development of this product produces letter cards that are needed in learning at the kindergarten level and are expected to be able to easily help students to be able to read at the beginning. In conclusion, the development of these letter cards can help increase student involvement in learning and help students to be able to read for starters. The development of this product has also gone through validation stages from media experts and material experts as well as individual trials which have shown positive results